Joining Forces to Combat Protracted Crises : Humanitarian and Development Support for Water and Sanitation Providers in the Middle East and North Africa - World Bank; ICRC; UNICEF (World Bank, Washington, DC, 2021)
Protracted crises in urban contexts of the Middle East and North Africa region present a growing challenge for water supply and sanitation (WSS) service providers and, in turn, the governments and international organizations that support them. The protracted nature of crisis in countries characterized by fragility, conflict, and violence (FCV) transcends conventional notions of (pre-, during, and post-) crisis management. This report examines five pernicious problems identified by WSS service providers operating in protracted crisis in the Middle East and North Africa region. The five problems are: (1) inadequately governed water resources management; (2) aggressive competition from alternative providers (tanker trucks), undermining network services; (3) paralysis of high-tech wastewater treatment plants; (4) escalating energy costs of off-grid generation; and (5) the cashflow crunch as service provider costs jump and revenues fall. The pernicious problems are shown to stem from precrisis vulnerabilities that have their origins in the rapid period of urbanization and infrastructure expansion across the Middle East and North Africa region. Humanitarian and development actors should strengthen their partnerships in both anticipating and responding to protracted crises. Strengthening humanitarian-development partnerships to support WSS service providers in these ways will address key aspects of precrisis resilience building and also of resilience (re)building in protracted crisis.